2007
DOI: 10.1002/ejlt.200700018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of supercritical CO2 and hexane extraction of lipids from sorghum distillers grains

Abstract: Total yields and compositions of sorghum dried distillers grains with solubles (DDGS) lipids obtained by supercritical CO 2 (SC-CO 2 ) extraction were compared with those obtained by recirculated solvent extraction (RSE) with hexane. The total yield of lipids obtained by SC-CO 2 extraction at 27.5 MPa and 70 7C was 150 g lipids/kg DDGS, while the yield obtained by RSE with hexane at 69 7C was only 85 g lipids/kg DDGS. The contents of four high-value compounds, i.e., policosanols, phytosterols, free fatty acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Studies have shown that higher concentrations of phytosterol can be extracted with scCO 2 than with soxhlet extractions using DCM or recirculated hexane extraction (Castola et al, 2005;Wang et al, 2007). The triterpenoid profile of the scCO 2 extract was found to be drastically different to that of the hexane soxhlet.…”
Section: Compoundsmentioning
confidence: 97%
“…Studies have shown that higher concentrations of phytosterol can be extracted with scCO 2 than with soxhlet extractions using DCM or recirculated hexane extraction (Castola et al, 2005;Wang et al, 2007). The triterpenoid profile of the scCO 2 extract was found to be drastically different to that of the hexane soxhlet.…”
Section: Compoundsmentioning
confidence: 97%
“…On comparison to the previously reported UAE using hexane for recovery of SQ from wine lees [11] the similarities found in the chemical composition of the obtained lipids is due to comparable hydrophobicity of SCCO 2 and hexane [36]. Yet, SCCO 2 was found to be superior to hexane as no oxidation products were evidenced.…”
Section: Characterization Of the Scco 2 Extractsmentioning
confidence: 49%
“…Sorghum grains are a relatively rich source of phytosterols when compared with fruits, vegetables, and other cereal grains commonly found in the food supply. Presently more than 200 sterols reported in vegetables, 3 have been identified in sorghum (sitosterol: 44.8 to 48.2%; campesterol: 26.1 to 38.0% and stigmasterol: 17.3% to 25.6%) (Wang et al 2007; Ye et al 2010).…”
Section: Bioactive Compounds In Sorghummentioning
confidence: 99%